THE ROLE AND CHALLENGES OF THE LOCAL ECONOMY IN ENSURING REGIONAL FINANCIAL SECURITY - Elmurodov Shohzod Shavkatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This analytical article examines the role of the local economy in ensuring regional financial security in the context of Uzbekistan. As the country advances its economic modernisation agenda, the importance of strong local economic structures becomes increasingly evident. The paper highlights how local enterprises, regional industries, and decentralised fiscal capacities contribute to financial resilience at the regional level. Using statistical data and regional case studies from Uzbekistan, the study identifies key challenges, including uneven economic development across regions, limited investment flows, weak infrastructure, and institutional inefficiencies. The analysis underscores the need for targeted policy reforms, capacity building, and improved coordination between local and central governments to strengthen the role of the local economy in achieving sustainable regional financial security.